The Influence of Fashion Innovativeness and Electronic Innovativeness on The Purchase Intention of Fashion Products Mediate by Brand Attitude - Murti, Anggun Cempaka; Setyawan, Anton Agus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This study examines the effect of fashion innovation and electronic innovation on purchase intention of fashion products mediated by attitude towards the brand. A quantitative approach was used by collecting data through an online survey to respondents in Indonesia who are interested in fashion and digital platforms. Study confirm that both fashion innovation and electronic innovation have a positive effect on purchase intention, with attitude towards the brand as a significant mediator. This study provides new insights into the combined effects of fashion and technological innovation on consumer purchasing behavior, and contributes to the literature related to consumer decision making in the digital era.